Analisis Yuridis Batasan Kewenangan Pelaksana Tugas dan Pelaksana Harian dalam Perspektif Asas-Asas Umum Pemerintahan yang Baik - Alacok Kahlasi, Maria Margaretha; Neonbeni, Randy Vallentino (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2025)
This study analyzes the juridical implications of the protracted practice of appointing Acting Officers (Plt) and Daily Executors (Plh) in government administration in Indonesia. Normatively, Acting and Acting Employees are temporary solutions based on the Mandate (Article 14 of Law No. 30/2014) to ensure the continuity of public services. However, the practice of appointment that exceeds the ideal time limit (maximum 6 months based on SE BKN No. 1/SE/I/2021) raises legality issues. Juridical analysis shows that the prolonged extension of the Plt/Plh harms the Principle of Legal Certainty and the Principle of Professionalism in the General Principles of Good Government (AUPB). The implication is that State Administrative Decrees (KTUN) issued outside the scope of the mandate, especially in the personnel aspect, are classified as Ultra Vires and have the potential to be null and void at the State Administrative Court (PTUN). Therefore, it is necessary to affirm administrative sanctions and strengthen the merit system supervision mechanism by the authorized institution (KemenPAN-RB/BKN or the Independent Supervisory Institution in place of KASN) to ensure that the filling of definitive positions runs on time, as well as ensuring the legitimacy of the issued KTUN.